2007
DOI: 10.1542/peds.2006-2258
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Gross Motor Function Measure for Use in Children and Adolescents With Traumatic Brain Injuries

Abstract: We demonstrate convincing evidence of responsiveness and validity to support the use of both Gross Motor Function Measure versions as evaluative measures of gross motor function in children and adolescents with traumatic brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 24 publications
1
41
0
2
Order By: Relevance
“…The GMFM-66 is derived from the GMFM-88 using Rasch analysis. Responsiveness to change in motor function using the GMFM-88 after pediatric TBI has been demonstrated in multiple studies (Kuhtz-Buschbeck et al, 2003;Linder-Lucht et al, 2007;Thomas-Stonell et al, 2006) and the GMFM-66 as well as the GMFM-88 have recently demonstrated sensitivity and discriminant validity, with excellent test-retest reliability, for use in children and adolescents with TBI (Linder-Lucht et al, 2007). The GMFM was validated with children and adolescents from 5 months to 16 years of age and is appropriate for children with motor skills at or below those of a 5-year-old child without motor disability.…”
Section: Physical Functioningmentioning
confidence: 99%
“…The GMFM-66 is derived from the GMFM-88 using Rasch analysis. Responsiveness to change in motor function using the GMFM-88 after pediatric TBI has been demonstrated in multiple studies (Kuhtz-Buschbeck et al, 2003;Linder-Lucht et al, 2007;Thomas-Stonell et al, 2006) and the GMFM-66 as well as the GMFM-88 have recently demonstrated sensitivity and discriminant validity, with excellent test-retest reliability, for use in children and adolescents with TBI (Linder-Lucht et al, 2007). The GMFM was validated with children and adolescents from 5 months to 16 years of age and is appropriate for children with motor skills at or below those of a 5-year-old child without motor disability.…”
Section: Physical Functioningmentioning
confidence: 99%
“…More sensitive, domain-specific instruments that have been validated for use in pediatric acquired brain injuries include measures of gross motor function, 21 functional independence, 22,23 health-related quality of life 24 and neuropsychological function. 25 Recent consensus statements 26 have suggested standardized "core data elements" that should be captured by all rehabilitation re searchers to allow the comparison and aggregation of rehabilitation outcomes.…”
Section: What Factors Determine Outcome After Acquired Brain Injury?mentioning
confidence: 99%
“…13,17 Motor deficits are an important characteristic of pediatric TBI and an indicator of recovery. Many motor function scales are currently used in children (Gross Motor Function Measure, Peabody Development Scales, Bruininks-Oseretsky Test of Motor Proficiency, Functional Reach Test), 7,8,[31][32][33] making the use of a motor proficiency scale in piglets an appropriate translational tool.…”
Section: Discussionmentioning
confidence: 99%